Multi-controllability of ambipolar photoconductivity in transition metal dichalcogenides van der Waals heterostructures - Elbanna, Ahmed (2023)
2D transition metal dichalcogenides (TMDs) and their van der Waals heterostructures possess great potential for optoelectronic applications thanks to their strong quantum confinement and flexibility in bandgap engineering. Photodetection based on TMDs utilizing photoconductance typically exhibits positive photoconductance resulting from the generation of photocarriers upon illumination. This study reports a SnSe2/MoS2 photodetector operating over a broadband range from deep ultraviolet to infrared wavelengths with not only a high responsivity and self-powered feature but also ambipolar photoresponse with both positive and negative photoconductances to multi-control parameters of wavelength, gate voltage, and laser power. The transition from positive to negative photoconductance by gate voltage and laser power indicates that charge recombination and interlayer exciton trapping result in negative photoconductance. The coexistence and controllable positive and negative photoconductance hold potential for multifunctional optoelectronic devices responding to multi-control parameters.